'Treating Africans differently': using skin colour as proxy for HIV risk. Issue 13 (22nd April 2016) - Henrickson, Mark; Fisher, Meaghan
Abstract : Aims and objectives: This paper examines the qualitative results of two studies of Black African new settler communities in New Zealand. The analysis investigates the issues of stigma and microaggressions and their effects on Black African communities. Background: Previous work that investigated experiences of stigma faced by relatively early Black African new settlers to New Zealand found that new settlers experienced stigma, and their resulting isolation had negative implications for access to health and social services, regardless of HIV status. Design: This paper is a meta‐analysis of two published studies, using original qualitative data from each. Methods: Researchers for the first study, Standing in the Fire, interviewed 13 Black Africans living with HIV who were new settlers to New Zealand. The second study, AfricaNZ Care, was a national mixed method study which surveyed 703 Black African new settlers, and included 131 participants in 23 different focus groups. The present analysis includes only the qualitative data from the second study. Some, but not most, participants of the second study were living with HIV. Results: Black African identity is used as a proxy for HIV status among non‐HIV specialist health care workers. Participants reported experiences of stigma and microaggressions based on their race, and a lack of knowledge about HIV in non‐HIV specialist nurses and other health care workers. They also experienced poor health care and education practices, professional prejudice against colleagues living with HIV and institutional challenges including failure to protect patient confidentiality. Conclusions: HIV‐related stigma and microaggressions remain significant problems, not only for people living with HIV but also for those perceived to be at high risk for HIV. Relevance to clinical practice: Experiences of stigmatising behaviour by health care professionals have a broad and significant range of impacts on patients' health outcomes.